Foresight study on dairy farming systems in Central Kenya and north of Senegal - Perin, Lucie; Enahoro, Dolapo (Frontiers in Sustainable Food Systems, 2023)
Dairy farming activities play a crucial role in Kenya and Senegal, in terms of nutrition and health, livelihoods, employment and culture. Facing various challenges such as climate change, increases of population and insecurity, and conflicts over resources (water, land, feed), dairy production systems will have to undergo changes in the future and adapt. This study used a qualitative foresight method that is based on interviews with technical experts and key stakeholders, including herders, to identify the main evolution trend to be observed in central Kenya and north of Senegal. It found that (semi)-intensification of production systems, and settlement of herders that used to be nomad pastoralists are the prevailing trends likely to persist in the future. For both countries, the key drivers of change and their potential environmental and socio-economic impacts were investigated. As dairy systems continue to face many challenges related to livestock feed and water availability, milk quality and safety, production costs, and market access, strategies are needed that improve resilience of the systems while attaining the right balance between productivity and sustainability